An Evaluation of the Contributions of European Union Education and Youth Programs to Schools: Case of Comenius Multilateral Projects - Fatma Kesik; Kadir Beycioğlu (Anı Publishing, 2020)
The primary aim of this qualitative study is to explore the opinions of teachers about the contributions of Comenius Multilateral Projects, included in the European Union Education and Youth Programs, to the schools. A phenomenology design was used in the study. Thirty teachers working in schools who have previously took part in Comenius projects participated in this study. The participants were selected on the basis of extreme/deviant sampling technique. The data were collected using semi-structured interviews and analyzed through content analysis. The results revealed that while Comenius projects were perceived as highly positive and contributed to participants' personal/professional, social, cultural development and language learning to a large extent; the contributions of these projects to the schools remained limited and were mostly in favor of the individuals taking active roles and participant institutions. Thus, it is suggested that the factors conveyed by the participants as problems should be taken into consideration in order to increase the contributions of the projects.